Influence of the Type Think Pair Share Cooperative Model Aided by Wordwall-Based Media on Mathematics Study Results of Class IV in Elementary School - Aini, Qurrota; Rapani, Rapani; Destiani, Frida; Hermawan, Jody Setya (Indonesian Journal of Education and Mathematical Science, 2025)
This research is motivated by the low learning outcomes in mathematics learning of fourth grade elementary school students. The purpose of this study was to determine the effect of the cooperative model of think pair share type assisted by wordwall-based media on student learning outcomes. The method used was quasi experimental type non-equivalent control group design. Data collection techniques are done through test and non-test techniques. Hypothesis testing using simple liner regression with the results showed that the application of the cooperative model of think pair share type assisted by wordwall-based media was able to increase students' active participation, understanding of mathematical concepts and learning outcomes significantly, so it can be concluded that there is a significant effect of using the cooperative model of think pair share type assisted by wordwall-based media on the learning outcomes of mathematics class IV elementary school.